Can new, improvised Visual Prostate Symptom Score replace the International Prostate Symptom Score? Indian perspective - K N Sanman; Ranjit Shetty; Rajeshkumar Reddy Adapala; Santosh Patil; GG Laxman Prabhu; P Venugopal (Indian Journal of Urology, 2020)
Introduction: Visual Prostate Symptom Score (VPSS) was introduced to overcome the drawbacks of the International Prostate Symptom Score (IPSS). However, this score also has potential for improvement. Materials and Methods: The primary objective of this study was to evaluate the utility of VPSS in patients with benign enlarged prostate (BEP) after uroflowmetric validation of the stream component. The secondary objective was to improve VPSS by adding a new severity grading and to assess if the "new upgraded VPSS" can replace IPSS in terms of ease of completion without assistance and the time taken. Results: Of 115 patients, 42.60% of them were of thea age group between 61– 70 years; mean ± standard deviation age was 64.75 years ± 8.042 (range 48– 90 years). Nineteen (16.52%) patients, who had education level ≥10th grade completed IPSS without assistance.. One hundred and eight (93.91%) patients completed VPSS without assistance (P = 0.000). None of those (0/6) with no formal education (but able to read and write) could complete the IPSS without assistance, whereas 66.67% completed the VPSS without assistance. Six minutes and two minutes was the average time taken to complete IPSS (4– 10 min) and VPSS (1– 3 min), respectively. Responses to different variables of VPSS were statistically significant (P < 0.001) compared to the IPSS. Correlation between the severity grading of the two scores was statistically significant (P < 0.001), with a statistically significant positive correlation between VPSS and IPSS (r = +0.582, P < 0.001). The new severity grading system developed on par with the IPSS, improvising the existing VPSS, showed statistically significant positive correlation to the IPSS (r = +0.587, P < 0.001). Conclusions : VPSS correlated well with IPSS. The "new improvised VPSS" developed by incorporating severity grading is a potential tool that can replace IPSS by overcoming its limitations.